Cysteine S-Glutathionylation Promotes Stability and Activation of the Hippo Downstream Effector Transcriptional Co-activator with PDZ-binding Motif (TAZ) - Gandhirajan, Rajesh Kumar (J Biol Chem, 2016)
Transcriptional co-activator with PDZ-binding motif (TAZ) and Yes-associated protein (YAP) are critical transcriptional co-activators downstream of the Hippo pathway involved in the regulation of organ size, tissue regeneration, proliferation, and apoptosis. Recent studies suggested common and distinct functions of TAZ and YAP and their diverse impact under several pathological conditions. Here we report differential regulation of TAZ and YAP in response to oxidative stress. H(2)O(2) exposure leads to increased stability and activation of TAZ but not of YAP. H(2)O(2) induces reversible S-glutathionylation at conserved cysteine residues within TAZ. We further demonstrate that TAZ S-glutathionylation is critical for reactive oxygen species (ROS)-mediated, TAZ-dependent TEA domain transcription factor (TEAD) trans-activation. Lysophosphatidic acid, a physiological activator of YAP and TAZ, induces ROS elevation and, subsequently, TAZ S-glutathionylation, which promotes TAZ-mediated target gene expression. TAZ expression is essential for renal homeostasis in mice, and we identify basal TAZ S-glutathionylation in murine kidney lysates, which is elevated during ischemia/reperfusion injury in vivo. This induced nuclear localization of TAZ and increased expression of connective tissue growth factor. These results describe a novel mechanism by which ROS sustains total cellular levels of TAZ. This preferential regulation suggests TAZ to be a redox sensor of the Hippo pathway.